Computer Accounting with Microsoft Office Accounting 2007 - Carol Yacht (McGraw-Hill, 2007)
Computer Accounting with Microsoft Office Accounting 2007 brings Carol Yacth and Susan Crosson's renowned step-by-step pedagogy to Microsoft's newest software for small business accounting. Students learn to manage the accounting activities of service and retail businesses.